«Senza metodo e senza imitazione». "Proemio" and "congedo" in the 17th century heroicomic poem (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The essay examines the figure of the narrator in poems that can be traced back to the varied galaxy of heroicomics and were composed within the first half of the 17th century. The analysis focuses in particular on the liminal zones of the canto (proemio and congedo) and tries to highlight the way in which each poet interprets the role of the narrative voice, attributing to it more or less frequently cognitive and/or metadiscursive functions, and sometimes giving it autobiographical traits. A multifaceted picture emerges, confirming the heterogeneity of the texts ascribed to the heroicomic genre and the different relationship in each work with the great 16th-century models of the Furioso and the Liberata
Keywords: heroicomic; parody; narrator; metadiscourse; satire; autobiography